Hand Hygiene Compliance in the ICU: A Systematic Review. Issue 9 (September 2019) - Lambe, Kathryn Ann; Lydon, Sinéad; Madden, Caoimhe; Vellinga, Akke; Hehir, Aoife; Walsh, Mary; O'Connor, Paul
Abstract : Objectives: To synthesize the literature describing compliance with World Health Organization hand hygiene guidelines in ICUs, to evaluate the quality of extant research, and to examine differences in compliance levels across geographical regions, ICU types, and healthcare worker groups, observation methods, and moments (indications) of hand hygiene. Data Sources: Electronic searches were conducted in August 2018 using Medline, CINAHL, PsycInfo, Embase, and Web of Science. Reference lists of included studies and related review articles were also screened. Study Selection: English-language, peer-reviewed studies measuring hand hygiene compliance by healthcare workers in an ICU setting using direct observation guided by the World Health Organization's "Five Moments for Hand Hygiene, " published since 2009, were included. Data Extraction: Information was extracted on study location, research design, type of ICU, healthcare workers, measurement procedures, and compliance levels. Data Synthesis: Sixty-one studies were included. Most were conducted in high-income countries (60.7%) and in adult ICUs (85.2%). Mean hand hygiene compliance was 59.6%. Compliance levels appeared to differ by geographic region (high-income countries 64.5%, low-income countries 9.1%), type of ICU (neonatal 67.0%, pediatric 41.2%, adult 58.2%), and type of healthcare worker (nursing staff 43.4%, physicians 32.6%, other staff 53.8%). Conclusions: Mean hand hygiene compliance appears notably lower than international targets. The data collated may offer useful indicators for those evaluating, and seeking to improve, hand hygiene compliance in ICUs internationally. Abstract : Supplemental Digital Content is available in the text.